(untitled) (Research, Society and Development, 2022)
Objective: To investigate the different levels of smartphone dependence in university students of Campina Grande - PB, on Covid-19 pandemic context. Methodology: This is a descriptive and quantitative study, and was made virtually on Google Forms. The present article evaluates the Smartphone Dependence Scale (SDS) and a Socioeconomic Questionnaire. Variables were analyzed by the Statistical Package for Social Sciences (SPSS) - 20.0. Results: in total, 155 students were included, 115 female and 40 male, with an average of 21.5±4,24 years old. The participants were categorized in four levels of dependence, according to SDS score, I-) No dependence II-) Low dependence, III-) Moderate dependence and IV-) High dependence. There was a gender divergence on the group of high dependence, so that 26,08% of women had high dependence, while just 10% of men were in this group. The average time reported by the sample was 7 hours and 6 minutes of smartphone daily usage. Conclusion: About 47,75% participants showed, even in moderate expressions, differents aspects of problematic usage, like restricted and compulsive use, social and emotional isolation, mood swing, sleep disturbance and problems on performing daily activities, with damages in the physical, psychic and social areas of life. It is considered that the habits of technology usage during the pandemic isolation accentuated the negative symptoms of dependence and problematic usage of smartphones.